The Effect of Motivation, Work Discipline, and Career Development on Civil Servant Performance Mediated by Job Satisfaction - A. Mashuri Djabiruddin; M. Mappamirirng; Yana Fajriah (Manunggal Halim Jaya, 2025)
This study aims to analyze the influence of motivation, work discipline, and career development on the performance of Civil Servants (ASN) through job satisfaction as a mediating variable at the Regional Revenue Agency of South Sulawesi Province. This research employs a quantitative approach, utilizing a survey method with data collected through questionnaires distributed to the entire population, comprising 55 respondents. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that motivation, work discipline, and career development have a positive and significant effect on team members' job satisfaction. Furthermore, job satisfaction has a positive and significant impact on the performance of civil servants. Additionally, job satisfaction significantly mediates the relationship between motivation, work discipline, and career development and performance. These findings underscore the importance of enhancing motivation, discipline, and career development as strategies to optimize employee performance and increase job satisfaction.